ANALISIS PENURUNAN HIDROGRAF SATUAN REPRESENTATIF - Nilna Amal (INFO-TEKNIK, 2013)
Indonesia has risk to get a flood event every year since big intensity rainfalls occur every year. Some waterworks will ‘be required to anticipate from it. The flood design number should be available. One of method which mostly used to be applied is unit hydrograph. Unit hydrograph concept firstly is defined by Sherman in 1932. It still be developed by many researchers to get any unit hydrograph basin both actual unit hydrograph and synthetic unit hydrograph. Since the characteristics of some unit hydrograph basin are specifics, researches to discover any unit hydrograph the basin are significant. This research attends to obtain the representative unit hydrograph of Bedog basin in Yogyakarta province. The result shows characteristics of representative unit hydrograph are depend on rainfall intensity due to its distributions and the flood hydrograph figure.